Penggunaan Macam Mulsa dan Air Kelapa dalam Peningkatan Hasil Bawang Merah (Allium ascalonicum L.) - Lara Nafrilla Sari; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The aim of this research was to get better yields of the true shallot (Allium ascalonicum L.) seed of Tuk Tuk variety on land that had been given plastic mulch and sprayed with coconut water. The research was carried out under the experimental garden shading net of the Faculty of Agriculture, Riau University, Pekanbaru, from July to October 2019, in split plot design experiment of simple random pattern with 3 replications. The main plot is a type of plastic mulch (M), consisting of: m1 = no mulch, m2 = silver black mulch, and m3 = silver mulch. The subplots was concentration of coconut water (K) as follows: k0 = 0%, k1 = 25%, k2 = 50%, and k3 = 75%. Variables observed were clump height, number of leaves per tuber, number of leaves per clump, tuber weight per clump, number of tubers per clump, tuber diameter, tuber height, weight of fresh tubers per plot and weight of dry tubers per plot. The observational data were analyzed of variance and Duncan New Multiple Range Test (DNMRT) at the 5% level. The results showed that no interaction between the type of mulch and the concentration of coconut water on the growth and production components of Tuk Tuk shallot seedlings. The growth components of the clump height and the number of leaves per clump, as well as the production components of tuber diameter and tuber height of the Tuk Tuk variety of shallots seedling is better if the plants are on land with silver mulch. The growth and production of the Tuk Tuk shallots seedlings  is not optimal because of weather disturbances and the shading net environment does not meet the growing requirements.Keywords: True Shallot Seed, mulch, coconut water